On Loranthus Control - Kadambi, K. (Indian Forester, 1954)
(Loranthus pulverulentus, Wall. Found on Dalbergia sissoo, has been effectively controlled by injecting small doses of copper sulphate and Fernoxone into the attacked trees. The note describes details of the method).